2021
DOI: 10.1016/j.jamda.2021.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Effects of the COVID-19 Pandemic on Nursing Home Resident Well-Being

Abstract: Objective: Quantify the effects of the COVID-19 pandemic on nursing home resident well-being. Design: Quantitative analysis of resident-level assessment data. Setting and participants: Long-stay residents living in Connecticut nursing homes. Methods: We used Minimum Data Set assessments to measure nursing home resident outcomes observed in each week between March and July 2020 for long-stay residents (eg, those in the nursing home for at least 100 days) who lived in a nursing home at the beginning of the pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 18 publications
(21 reference statements)
4
89
0
Order By: Relevance
“…More so, given the surveillance of their relative by family members, one can conclude that the impact of restrictions on residents was also having consequences on their physical and cognitive health. This is not surprising, because the presence of family members not only improves the quality of life of residents in LTC (Levere et al, 2021;Stall et al, 2020;Tupper et al, 2020) but also supports the role of staff (Bouchoucha & Bloomer, 2021). Based on our comparison of phase I and phase II results, our study clearly illustrates the positive influence of families' continued presence in LTCFs on multiple aspects of older adults' health and that they are essential members of the care team.…”
Section: Discussionsupporting
confidence: 61%
“…More so, given the surveillance of their relative by family members, one can conclude that the impact of restrictions on residents was also having consequences on their physical and cognitive health. This is not surprising, because the presence of family members not only improves the quality of life of residents in LTC (Levere et al, 2021;Stall et al, 2020;Tupper et al, 2020) but also supports the role of staff (Bouchoucha & Bloomer, 2021). Based on our comparison of phase I and phase II results, our study clearly illustrates the positive influence of families' continued presence in LTCFs on multiple aspects of older adults' health and that they are essential members of the care team.…”
Section: Discussionsupporting
confidence: 61%
“…We found that nursing home residents will have a low symptom burden but will still have some indicator of infection. The long symptom burden necessitates prolonged isolation, extensive use of PPE and can significantly impact the quality of life of this patient population 24 . Although the disease course of COVID‐19 may be difficult to predict and leads to increased mortality, most residents infected with COVID‐19 can be managed in the nursing home with appropriate staff and resources, including abundant PPE and testing capacity.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Residents’ social relationships with each other, staff, and visitors provides a sense of belonging and significance and social relationships are important for overall well-being. 25 , 26 , 27 By removing physical relationships with visitors and replacing this relationship with a virtual option, some residents might have felt a lost in their relationships and had a decreased sense of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining resident's perspectives of video conferencing could assist SNFs with understanding the sustainability of continuing this intervention. 24 Finally, more research is needed to capture the SNF communities’ stories or lived experience 26 during this pandemic. Capturing stories from residents, staff, and visitors would add compelling descriptions of what it has been like to live in and survive the COVID-19 pandemic within one of the most high-risk settings.…”
Section: Discussionmentioning
confidence: 99%